Peranan Pembantu Rumah Tangga Bagi Karier Wanita Pendidik - Tri Irawati Didik Nugroho (Jurnal Ilmiah SINUS, 2008)
Result of survey to 100 woman lecturer in Surakarta region, by making 2 variable that is independent and dependent. Result from research of independent variable have influence with irrespective storey;level sequence assistant, mount contiguity child with assistant, mothering pattern, and contiguity storey level. While to waston durbin do not happened autocorelation because coming near value 2 that is 1,932. With anova can be known by strength storey, level or influence from both variable with significant value 0,045 meaning less than 0,05 hence having strong influence between independent variable and its meaning dependen variable housemaid role have strong influence with educator woman career specially lecturer. And f value calculate equal to 2,485 or 2,485 > 2,465 which its meaning there is relation which is significant between educator woman career with housemaid role Keyword : Housemaid, Career Woman Educator